Soil management: introduction of tillage in a vineyard with a long-term natural cover - Cruz, Amândio (2012)
A study was carried out during two years (2004 and 2005) at Bairrada Delimited Region (littoral/centre of Portugal) with the white cultivar “Fernão Pires” for the evaluation of the effects of tillage application in a non-irrigated commercial vineyard with a long term natural cover crop. In the two years of the experiment, during the growing season the climate was dry, especially in 2005. Consequently, a moderate to severe water stress was observed during ripening,, although little differences between natural grass covered and tilled treatments were found, according to predawn leaf water potential evolution. Vine nutritional status was also improved by tillage and, therefore, higher net photosynthetic rates were verifi ed. Tillage induced higher vegetative growth, particularly on lateral shoots that led to a denser and more shaded canopy. Hence bunch rot (Botrytis cinerea Pers.) intensity was signifi cantly higher in the tilled treatment in 2004 due to important rainfall events in summer. However, in hot and dry summers, as in 2005, higher vigour induced by tillage was crucial to reduce bunch sunburn injuries. The yield was signifi cantly increased in 2005 in tilled treatment (around 100%) because of higher fertility index, which result from the better nutritional status and vigour of previous year, bunch and berry weight, and also from the decrease of sunburn injuries. Lower effects of treatments were observed in the must composition. In 2005, even with a strong yield increase caused by tillage, the soil management techniques did not infl uenced the nutritional must composition.